Literatur Review Pembelajaran Instalasi Penerangan Listrik Melalui Sarana Media Google Sites - Balqis Az Zahra; Joko; Fendi Achmad; Muhamad Syariffuddien Zuhrie (Jurnal Pendidikan Teknik Elektro, 2026)
Learning Electrical Lighting Installation (IPL) at Vocational High Schools (SMK) requires a combination of practical skills and theoretical understanding. However, the learning process is dominated by conventional media, which does not support interactive and independent learning. With the advancement of digital technology, Google Sites may be an effective educational platform due to its ability to combine materials, project-based learning activities, and multimedia. The objective of this study is to synthesize research findings on learning electrical lighting installation using Google Sites media. A Systematic Literature Review (SLR) based on the PRISMA guidelines was conducted for the research, encompassing phases such as identification, screening, eligibility, and ultimate selection. Literature searches were conducted through Google Scholar, SINTA, and educational journal databases with publications ranging from 2021 to 2025. The final selection yielded nine relevant articles, which were analyzed based on the variables of student response and learning outcomes. The results of the study indicate that employing Google Sites in education, particularly when combined with interactive learning approaches like project-based and discovery learning, can enhance student engagement, drive comprehension of concepts, and improve academic performance. Thus, Google Sites can be recommended as an effective alternative digital learning medium to support the teaching of electrical lighting installation in vocational schools.